1995
DOI: 10.1038/377630a0
|View full text |Cite|
|
Sign up to set email alerts
|

A role for CD95 ligand in preventing graft rejection

Abstract: Testis is a remarkable immune-privileged site, long known for its ability to support allogeneic and xenogeneic tissue transplants. Here we have investigated the molecular basis for testis immune privilege. Testis grafts derived from mice that can express functional CD95 (Fas or Apo-1) ligand survived indefinitely when transplanted under the kidney capsule of allogeneic animals, whereas testis grafts derived from mutant gld mice, which express non-functional ligand, were rejected. Further analysis of testis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
607
3
8

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,105 publications
(636 citation statements)
references
References 29 publications
18
607
3
8
Order By: Relevance
“…Fas ligand (FasL), a type II membrane protein, belongs to the tumor necrosis factor (TNF) superfamily. FasL is expressed by activated T lymphocytes, natural killer (NK) cells, and a small number of non-lymphoid cells (5), suggesting that Fas-FasL system may play an important role in the privileged status (6). These findings may indicate that gene transfer of FasL induces apoptotic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Fas ligand (FasL), a type II membrane protein, belongs to the tumor necrosis factor (TNF) superfamily. FasL is expressed by activated T lymphocytes, natural killer (NK) cells, and a small number of non-lymphoid cells (5), suggesting that Fas-FasL system may play an important role in the privileged status (6). These findings may indicate that gene transfer of FasL induces apoptotic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Sertoli cells, epithelial cells of the anterior chamber of the eye and some types of tumor cells, such as melanoma and colon cancer cells which express FasL, as well as myoblasts engineered to produce FasL can create an immunoprivileged environment. [13][14][15][16][17][18] Allogenic CT26 colon carcinoma cells expressing mouse FasL markedly reduced allogenic cytotoxic T lymphocytes and completely inhibited generation of alloantibodies of both IgM and IgG subclasses. 26 In contrast with these experimental findings, the presence of FasL on the surface of allogenic pancreatic islets failed to protect these islets from allogenic rejection and this reaction was found to involve the formation of a granulocytic infiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The presence of FasL confers immunological privilege to these cells and allo-or xenografts transplanted into these sites are not rejected since FasL expressed by Sertoli cells and epithelial cells of the anterior chamber of the eye induce death of infiltrating T cells expressing high levels of Fas. 15 Lau and co-workers 16 reported that syngenic myoblasts engineered to express FasL could delay rejection of pancreatic islet allografts when transplanted under the kidney capsule. Recently, expression of FasL was found on some tumor cells such as melanoma, colon…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This immunoprotective environment is due in part to the secretion of immunosuppressive molecules by Sertoli cells (SCs) [5][6][7] that allow ectopically transplanted SCs to survive as allografts [8][9][10] and concordant (rat-to-mouse) 11 and discordant (pig-to-rat) 12,13 xenografts in rodents. In addition to the ability of transplanted SCs to protect themselves in immunologically foreign environments, SCs were shown to protect islets and neuronal cells from immunemediated rejection.…”
Section: Introductionmentioning
confidence: 99%